Turbulent forced convection and entropy analysis of a nanofluid through a 3D 90° elbow using a two‐phase approach. Issue 8 (5th August 2021) - Korei, Zakaria; Benissaad, Smail
Abstract: In a scenario characterized by a secondary flow called Dean's vortices, thermal and flow behavior analysis is examined. Forced convection of an Al2 O3 –water nanofluid through a three‐dimensional (3D) 90° elbow was analyzed numerically using a multiphase mixture model. Turbulence is taken into account by using the shear‐stress transport k – ω model. Also, entropy production is presented to obtain the optimized conditions. Simulation parameters consist of different Reynolds numbers (10, 000   ≤   Re   ≤   100, 000), nanoparticle volume fraction ( 2 % ≤ ϕ ≤ 6 % ), nanoparticle diameter ( 10 ≤ d p ≤ 40 ) . The findings reveal that the increase in the ϕ and the Re along with a smaller dp discourages the appearance of Dean vortices in the flow. The pressure drop increases with the increase in the volume fraction and the decrease in the nanoparticles' diameter. The highest NuM is observed at ϕ = 6 % for d p = 10   nm . Significant heat transfer rates are observed near the outer wall. The minimum total entropy production is obtained at Re  = 100, 000 for ϕ = 2 % and d p = 40   nm .